The acute: chronic workload ratio is associated with injury in junior tennis players - Myers, N. L.; Aguilar, K. V.; Mexicano, G.; Farnsworth, J. L.; Knudson, D.; Kibler, W. B. (Medicine & Science in Sports & Exercise, 2020)
Purpose: Session RPE (sRPE) is used to track internal training/competition load in athletes using a metric known as the acute to chronic workload ratio (ACWR). Research that reported on team sports has determined that if the acute load is higher than the chronic load, athletes are likely to sustain injury. No studies, however, have attempted to investigate internal load and injury in a tennis population despite the rigorous training loads. Therefore, the purpose of this study was to investigate if sRPE ACWR is associated with injury in junior tennis players over a 7-month time period.